Standardization of Ginger and Javanese Turmeric Crude Drugs and Total Flavonoid and Phenolic Content Profiles of Their Combination - Hartanti, Dwi; Hamad, Alwani (JRST (Jurnal Riset Sains dan Teknologi), 2024)
A combination of ginger (Zingiber officinale Roscoe) and Javanese turmeric (Curcuma zanthorrhiza Roxb.) rhizomes is used by Baturraden, Central Java, people to treat an ailment called masuk angin. This study aimed to evaluate the quality profile of ginger and Javanese turmeric crude drugs and determine the total flavonoid content (TFC) and the total phenolic content (TPC) of combinations of both crude drugs in five different weight ratios. Standardization of crude drugs used parameters, methods, and standards of the compendial Indonesian Herbal Pharmacopeia (IHP). Ginger crude drugs met the standard in parameters of morphology, loss on drying, acid-insoluble ash, ethanol extractable, and water extractable, while morphology and values of loss on drying, acid-insoluble ash, ethanol extractable, water extractable, and volatile content of Javanese turmeric were within their respective specifications. The TFC of Javanese turmeric is lower than that of ginger, but the opposite trend was observed for TPC. The crude drug weight ratio significantly affected the TFC and TPC of the ginger and Javanese turmeric combination. The combination with the highest TFC and TPC was Formula IV (7.11±0.37 mg Quercetin equivalent (QE)/g) and Formula II (21.65±1.49 mg Gallic acid equivalent (GAE)/g), respectively.  Our study suggested that ginger and Javanese turmeric crude drugs were not of good quality, and their mixture in weight ratio of 25-75 provided the highest TPC warrant for further bioactivity evaluations.